(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Macrophages, as the first defense mechanism in Mycobacterium tuberculosis infection, play the important role in pulmonary TB pathogenesis. The increasing prevalence of pulmonary TB is followed by the increasing prevalence of diabetes mellitus (DM). DM patients have 4,7 times higher risk to develop pulmonary TB compared to patients without DM, since DM can increase the frequency and severity of an infection, including pulmonary TB. Aim: To analyze macrophage activity (phagocytosis, intracellular killing, and IFN-γsynthesis) of TBDM and TB non-DM patient. Method: This experimental study used a PBMC cultured sample from TB-DM and TB non-DM patient’s which undergo observation of macrophage activity (phagocytic, intracellular killing and IFN-γsynthesis). The data were taken from microscopic observation of TB-DM and TB non-DM patients, colony growth of viable M. tuberculosis and the IFN-γlevel secreted by macrophages. Result: The result showed that macrophages of TB-DM patient’s were less amount of phagocytosedM. tuberculosis, a little amount of formed vacuoles and giant cells, secrete low level of IFN-γ, and more viable M. tuberculosis(from subculture). Conclusions: Macrophages of TB-DM patients are reduced phagocytic activity toward M. tuberculosis which is this macrophages are less activated. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.107-111